Unveiling the hidden risk of caspofungin: insights from three adverse event reporting systems and network pharmacology integration - Li, Zhengfu; Cui, Zhiwei; Xie, De; Zou, Fan; Zhu, Chengyu (Frontiers in Pharmacology, 2025)
BackgroundCaspofungin, the first FDA-approved echinocandin antifungal agent, plays a vital role in managing invasive fungal infections (IFIs). Despite its established efficacy, large-scale real-world safety evaluations remain limited. This study provides a comprehensive pharmacovigilance analysis of caspofungin’s safety profile.MethodsAdverse drug events (ADEs) associated with caspofungin were extracted from the FDA Adverse Event Reporting System (FAERS), the Japanese Adverse Drug Event Reporting Database and the Canadian Vigilance Adverse Reaction Database (CVARD) databases. Signal detection utilized four methods: reporting odds ratio proportional reporting ratio Bayesian confidence propagation neural network and multiple gamma-Poisson shrinkage Time-to-onset (TTO) analysis was conducted using FDA Adverse Event Reporting System data, and network pharmacology approaches were employed to investigate potential molecular mechanisms, particularly in caspofungin-related liver injury.ResultsA total of 2,270, 161, and 128 ADE reports were retrieved from FAERS, JADER, and CVARD, respectively. “Hepatobiliary disorders” and “infections and infestations” are overlapping positive signals from three databases at the system organ class level. ADEs such as hypokalemia, sepsis, and drug ineffectiveness were consistent with the drug label. Unexpected signals included prolonged QT interval, cardiac arrest, septic shock, and cholestasis. Cross-database overlap included “drug ineffective” and “toxic skin eruption” between FAERS and JADER, and “renal failure,” “photodermatitis” between FAERS and CVARD. TTO analysis revealed that 89.95% of ADEs occurred within the first month, with a median onset time of 6 days. Network pharmacology identified PI3K/Akt and HIF-1 pathways as mechanisms underlying caspofungin-induced liver injury.ConclusionThis study highlights both expected and unexpected ADEs of caspofungin, emphasizing the importance of clinical vigilance and molecular research to enhance patient safety and therapeutic outcomes.